China, South Africa and the Lewis Model - Knight, J (2007)
The paper uses the Lewis model as a framework for examining the labour market progress of two labour-abundant countries, China and South Africa, towards labour shortage and generally rising labour real incomes. In the acuteness of their rural-urban divides, forms of migrant labour, rapid rural-urban migration, and high and rising real wages in the formal sector, the two economies are surprisingly similar. They differ, however, in the dynamism of their formal sector growth of output and employment, and in the growth of their labour forces. Whereas China - a labour-surplus economy par excellence despite unemployment until recently taking only a disguised form - is moving rapidly in the direction of labour scarcity, South Africa - which historically has been short of labour - is moving towards increased labour surplus in the form of open unemployment. The paper draws on research previously conducted by the author in separate research projects on the two countries.